Rancang Bangun Kapasitor Bank Otomatis Berbasis Mikrokontroler ATmega 328P Untuk Perbaikan Faktor Daya - Putu Angga Juliantara; I Wayan Arta Wijaya; Cok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2018)
Inductive load with low power factor has led to the greater load current so that it is required a power factor improvement. Improvement of power factor in inductive load can be carried out by installing capacitor according to required proportion. Installation of capacitors can be used in parallel or series to electric source.The method of making design is divided into two parts, namely, the first is the designing of hardware and the second is the designing of the software. The designing of hardware consists of designing the power supply circuit, driver relay circuit, LCD circuit, minimum system circuit of ATmega 328P, capacitor bank circuit, current sensor circuit and voltage sensor circuit. The sensors used in this study were a non-invasive type SCT013-010 current sensor and a voltage sensor of a 500 mA type zero transformer. The design of software was in the form of work program tools that use the application of Arduino IDE. LCD displays the readout values of voltage, load current, active power, apparent power, reactive power and power factor. The ATmega 328P microcontroller processes data and determines the working relay so that the purpose of power factor value by cos phi ? 0.85 is achieved. The results achieved in this research is the design of automatic bank capacitor based on microcontroller of ATmega 328P can improve power factor by conducting injection capacitor to raise the power factor value according to PLN standard by cos phi ? 0.85 by connecting capacitor to the source of PLN paralleled by a single phase inductive load.